Certifying CMMI-DEV in the Context of Model-Driven Software Engineering - Pons, Claudia (2018)
Model-driven software engineering (MDE) is being positioned as an alternative to conventional methods of software production. Given that MDE is an emerging paradigm, standards for measuring its quality have not yet been established. This article analyzes MDE good practices and how they relate to CMMI-DEV 1.3 Level 2. MDE best practices were assessed to determine whether they support each CMMI Level 2 specific practice in seven of the 22 process areas: configuration management, supplier agreement management, requirement management, process and product quality assurance, measurement and analysis, project monitoring and control, and project planning. An expert panel of five software engineering professionals offered consulting services to provide an initial evaluation of the results. For each process area, the percentage of practices supported by MDE was determined and recommendations to enhance MDE support were identified. Although further research is needed, this suggests that an organization that uses MDE can certify at CMMI-DEV 1.3 Level 2.